If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 + -2x = 2x + -10 Reorder the terms: 2 + 6x + -2x = 2x + -10 Combine like terms: 6x + -2x = 4x 2 + 4x = 2x + -10 Reorder the terms: 2 + 4x = -10 + 2x Solving 2 + 4x = -10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + 4x + -2x = -10 + 2x + -2x Combine like terms: 4x + -2x = 2x 2 + 2x = -10 + 2x + -2x Combine like terms: 2x + -2x = 0 2 + 2x = -10 + 0 2 + 2x = -10 Add '-2' to each side of the equation. 2 + -2 + 2x = -10 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = -10 + -2 2x = -10 + -2 Combine like terms: -10 + -2 = -12 2x = -12 Divide each side by '2'. x = -6 Simplifying x = -6
| y=ln(x^2+k)+ln(x^2+9-k) | | 12y+34x=1216 | | 11-t/2=t/3-4 | | 6=-3x+3 | | 1/3/3/5=5/2/n | | X/5=3.8 | | 2/3x+4=2/28 | | 7j=-9+6j | | -6+2y=4y+10 | | 14=800X-5E-15 | | (x+2)*x+3=24 | | 1/3-1/9x=-5/3 | | 2/11y+1/4=1/11y+8/5 | | 2ac-3bc-6bd+4ad=0 | | ac-3bc-6bd+4ad=0 | | (6x+8)(5x^2+9x+2)= | | x*x+7x+5=0 | | 5x^2+51x-360=0 | | -9p-7=10p | | x^4+2x^3=21-14x-4x^2 | | 9xy^4-xz^2=0 | | 2y^4=11y^2-12 | | f(5)=7(5)-22/4 | | Tan3.14/12 | | X+58=120 | | X-25=80 | | 9y-38=-8(y-8) | | (9x^2-5x-42)+(4x^2+7x)= | | -3x+5=-6x+14 | | (-3)+x=10 | | (2x+5)(6-3x)=0 | | 7x+4y+2z=1650 |